2005
DOI: 10.1182/blood-2005-02-0838
|View full text |Cite
|
Sign up to set email alerts
|

SDX-101, the R-enantiomer of etodolac, induces cytotoxicity, overcomes drug resistance, and enhances the activity of dexamethasone in multiple myeloma

Abstract: In this study we report that R-etodolac (SDX-101), at clinically relevant concentrations, induces potent cytotoxicity in drugsensitive multiple myeloma (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 70 publications
1
42
1
Order By: Relevance
“…Thus, it is attractive to consider alternate agents that lack the adverse consequences of COX-2 inhibition. R-Etodolac has been shown to have antitumor effects in several cancer cell lines and lacks COX-inhibitory activity [21][22][23]. Our results demonstrate that R-Etodolac inhibits survival and proliferation of HCC cells lines in a dosedependent manner and may be potentially useful in HCC treatment or chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, it is attractive to consider alternate agents that lack the adverse consequences of COX-2 inhibition. R-Etodolac has been shown to have antitumor effects in several cancer cell lines and lacks COX-inhibitory activity [21][22][23]. Our results demonstrate that R-Etodolac inhibits survival and proliferation of HCC cells lines in a dosedependent manner and may be potentially useful in HCC treatment or chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 69%
“…Therapeutic use of the R-Etodolac, therefore, offers the potential advantage of minimizing COX-dependent side effects. Antineoplastic effects of R-Etodolac have been recently shown in chronic lymphocytic leukemia (CLL), multiple myeloma, and prostate cancer [21][22][23]. Here, we demonstrate the anti-β-catenin properties of Celecoxib at high doses and of R-Etodolac at physiological doses on hepatoma cell lines, which was associated with their diminished survival and proliferation.…”
Section: Introductionmentioning
confidence: 64%
“…47 Moreover, R-etodolac, an enantiomer of the NSAID etodolac lacking COX inhibitory activity, has cytotoxic activity against CLL, 6 prostate cancer 48,49 and MM. 3,50 In this study, we demonstrated that the novel etodolac derivative SDX-308 inhibits b-catenin/TCF pathway and induces MM cytotoxicity, without significant COX inhibition. As side effects related to inhibition of COX-1 (gastrointestinal and renal toxicity) and COX-2 (cardiovascular toxicity) can be dose limiting, the strategy to develop and use COX-independent NSAID derivatives like SDX-308 as cancer chemopreventive and chemotherapeutic agents is promising.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 We recently reported that the R-enantiomer of etodolac (R-etodolac/SDX-101), a non-COX inhibitor currently under investigation in phase 2 clinical trials for treatment of refractory chronic lymphocytic leukemia (CLL), induces potent cytotoxicity at clinically relevant concentrations in conventional drug-sensitive and drug-resistant multiple myeloma (MM) cell lines, as well as in patient MM tumor cells. 3 SDX-308 (CEP-18082), a novel analog of etodolac, has more potent cytotoxicity than R-etodolac in several cancer cell lines including colon, prostate, ovarian and breast cancer, Recent studies have shown that NSAIDs including R-etodolac inhibit b-catenin-dependent transcription in malignant cells; however, its mechanisms of action has not yet been fully defined. [4][5][6][7] Specifically, the colonic polyps of patients treated with NSAIDs have reduced nuclear accumulation of b-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to disregulation of HOX genes, other signaling pathways are perturbed by MLL-translocations and may contribute to leukemogeneis. For example, transcriptional deregulation of FMS-like tyrosine kinase 3(FLT3), glycogen synthase kinase 3 (GSK3), heat shock protein-90 (HSP-90), myeloid cell leukemia sequence-1 (MCL-1), and components of the RAS pathway have been implicated in MLL1-induced leukemogenesis Brown et al, 2005;Carnicer et al, 2004;Liang et al, 2006;Stubbs et al, 2008;Wang et al, 2008;Yao et al, 2005;Yasui et al, 2005;Yocum et al, 2006). MLL1's role as a master regulator of gene expression significantly complicates understanding its role in MLL1 associated leukemogenesis.…”
Section: Pathogenesis Of Acute Leukemias With Mll1-translocationsmentioning
confidence: 99%